Modelos de gestão e inovação social em organizações sem fins lucrativos: um estudo comparativo de casos no Brasil e no Québec - Rodrigues, Andréa Leite (2004)
This work is in the field of studies regarding non-profit organizations. Over the last two decades of the 20th Century, such organizations saw a large increase in revenues, workload and media exposure. Such a growth was motivated by sociopolitical, socioeconomic and sociodemographic issues. One could see that such a growth was accompanied by changes in their management models, especially the organizational and governance structures. The main objective of this work is to develop upon relations between non-profit organization management models and the generation of social innovation. The theoretical concept was based upon a bibliographical review of the following concepts: the non-profit sector, of an Anglo-Saxon origin, social economy, of a French origin, organizational innovation and social innovation. It is a qualitative, exploratory study, where the means of investigation are two case-studies of non-profit organizations. The case studies involved field research, document examination, personal observation and interviews with key-players in the respective organizations. The first case was at an association located in Sao Paulo, Brazil, with its arts school; the other, is a solidarity-based cooperative located in Montreal, Québec, Canada. At the end of the work, the results of the analyses on the relations between management models and the generation of social innovation are put forward.